The effectiveness of the discovery and expository approaches in the teaching of social studies in a high school in Quezon City - Parentela, Belinda B. 1951-
The study determined the extent to which the discovery approach is more effective than the expository approach on the following aspects: (1) acquisition of factual information; (2) retention of factual information; (3) developing students' thinking skills; and (4) fostering desirable attitudes. Its implications on the instructional production in the social studies and on pre-service and in-service training of social studies teachers were also analyzed.